2018
DOI: 10.1111/ppa.12826
|View full text |Cite
|
Sign up to set email alerts
|

Screening tomato genotypes for resistance and tolerance to Tomato chlorosis virus

Abstract: Tomato chlorosis virus (ToCV) is an emerging crinivirus in Brazil that causes an economically important disease in tomato (Solanum lycopersicum) and other solanaceous species. ToCV is transmitted predominantly by the whitefly Bemisia tabaci Middle East‐Asia Minor 1 (MEAM1, formerly biotype B), in a semipersistent manner. As all cultivated tomato varieties and hybrids are susceptible to this crinivirus, the main alternatives for the control of the disease are the use of healthy seedlings for transplanting and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
0
16
0
7
Order By: Relevance
“…Virus-and whitefly-free tomato transplants of cultivars resistant to begomovirus infection were used in all fields: Dominador (TopSeed) in Goian apolis, An apolis and Taquara, as well as Predador (Top-Seed) in Boa Esperanc ßa. By carrying the Ty-1 resistance gene, both Dominador and Predador are moderately resistant to begomovirus infection; however, Dominador is moderately resistant, and Predador is highly susceptible to ToCV infection (Mansilla-C ordova et al, 2018). In these plants, the infection rate to Brazilian begomoviruses (e.g.…”
Section: Location Experimental Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus-and whitefly-free tomato transplants of cultivars resistant to begomovirus infection were used in all fields: Dominador (TopSeed) in Goian apolis, An apolis and Taquara, as well as Predador (Top-Seed) in Boa Esperanc ßa. By carrying the Ty-1 resistance gene, both Dominador and Predador are moderately resistant to begomovirus infection; however, Dominador is moderately resistant, and Predador is highly susceptible to ToCV infection (Mansilla-C ordova et al, 2018). In these plants, the infection rate to Brazilian begomoviruses (e.g.…”
Section: Location Experimental Design and Data Collectionmentioning
confidence: 99%
“…The control of golden mosaic disease usually relies on the use of resistant tomato cultivars and frequent applications of insecticides for vector control , while chemical spraying is the major control method used for the yellowing disease, due to the absence of resistant cultivars (Mansilla-C ordova et al, 2018). Even though tomato growers in Brazil usually spray insecticides to combat whiteflies two or three times per week to prevent the spread of both viruses, the high incidence of the diseases caused by ToSRV and ToCV demonstrates that this strategy has low efficacy .…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no commercial tomato cultivar reported to be resistant or tolerant to ToCV. However, experiments carried out in Spain, Brazil and Uruguay have identified several wild tomato species ( Solanum section Lycopersicon ) that contain genotypes reacting with mild symptoms and/or low viral titres to the natural or experimental inoculation with ToCV (García‐Cano et al , ; González‐Arcos et al , ; Mansilla‐Córdova et al , ). The most promising materials include genotypes of S. chmielewskii , S. habrochaites and S. lycopersicum × S. peruvianum .…”
Section: Control Strategiesmentioning
confidence: 99%
“…For plants inoculated 75 days after transplanting, a yield reduction of about 6.3% was observed in only one experiment. Mansilla-C ordova et al (2018), analysing the tolerance of 18 tomato genotypes to the yellowing disease caused by ToCV, reported that the reduction in plant development, based on the dry weight of the aerial part and on fruit yield ranged from 1.4% to 67.6% and 0.1% to 51.8%, respectively, compared to healthy plants of each genotype.…”
Section: Single Virusmentioning
confidence: 99%